2021
DOI: 10.1177/21676968211034309
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the Benefits of Bicultural Competence: Latina/x/o College Students’ Academic and Psychosocial Adjustment

Abstract: Theories posit that bicultural competence, the ability to negotiate between U.S. mainstream culture and one’s own heritage culture, is an important cultural adaptation skill for Latina/x/o populations’ academic and psychosocial outcomes, in part, because of the ability to hold and resolve competing perspectives within and across contexts. However, more research is needed to identify the associations of distinct dimensions of bicultural competence to academic and psychosocial adjustment. The current study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 72 publications
1
16
0
1
Order By: Relevance
“…In support of Hypothesis 2, we found that youth who demonstrated greater levels of bicultural competence across this period (high school to fourth college semester), as evidenced by higher intercepts or more positive slopes (suggesting stability or growth), exhibited greater academic engagement and self‐efficacy in their fifth college semester. These findings extend prior empirical, cross‐sectional work documenting a positive link between indicators of biculturalism and U.S. Latinos' academic perceptions, aspirations, and achievement (e.g., Acevedo‐Polakovich et al, 2014; Carbajal et al, 2021; Chun et al, 2016). Additionally, they extend prior longitudinal work documenting that indicators of biculturalism may set youth into more positive academic trajectories in college (Rivas‐Drake & Mooney, 2009).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In support of Hypothesis 2, we found that youth who demonstrated greater levels of bicultural competence across this period (high school to fourth college semester), as evidenced by higher intercepts or more positive slopes (suggesting stability or growth), exhibited greater academic engagement and self‐efficacy in their fifth college semester. These findings extend prior empirical, cross‐sectional work documenting a positive link between indicators of biculturalism and U.S. Latinos' academic perceptions, aspirations, and achievement (e.g., Acevedo‐Polakovich et al, 2014; Carbajal et al, 2021; Chun et al, 2016). Additionally, they extend prior longitudinal work documenting that indicators of biculturalism may set youth into more positive academic trajectories in college (Rivas‐Drake & Mooney, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…For instance, youth's frequent need to transition between cultural frames of reference could prove, in part, behaviorally, cognitively, and socially taxing unless youth are embedded in contexts that are supportive, inclusive, and culturally relevant (Safa et al, 2019). Thus, college settings may promote youth bicultural competence, and this may support youth adaptation to college (e.g., developing positive relationships with peers; Carbajal et al, 2021); however, the additional behavioral, cognitive, and social challenges associated with managing new bicultural demands in settings in which host versus heritage culture competencies may be differentially valued (Darder, 2015) may also have some costs to youth's academic adjustment (e.g., lower GPA).…”
Section: Bicultural Competence Development and Academic Adjustmentmentioning
confidence: 99%
“…In Mexican‐origin families of 10‐year‐olds, Safa et al (2021) found that PAS operated via disrupted parental ethnic socialization to negatively affect child bicultural competence. In light of research that highlights the benefits of culturally based developmental assets such as (bi)cultural competence and ethnic identity (Carbajal et al, 2021), more research is needed to (dis)confirm the harmful influence of PAS on bicultural competence that Safa et al's findings suggest. We also need studies that examine what, if any, role PAS may play in Latinx youth's ethnic identity development.…”
Section: Methodological Approachmentioning
confidence: 96%
“…Mexican only 9 Calzada et al, 2019;Helms et al, 2014;Leidy et al, 2009;Rusch & Reyes, 2012;Safa et al, 2021;Umaña-Taylor et al, 2011;Wu et al, 2020;Zeiders et al, 2015;Zeiders et al 10 Calzada et al, 2019;Leidy et al, 2009;Mendoza et al, 2017;Safa et al, 2021;Umaña-Taylor et al, 2011;White et al, 2009;Williams et al, 2017;Wu et al, 2020;Zeiders et al, 2015;Zeiders et al…”
Section: Applying the Fsm To Parental Acculturative Stress And Latinx...unclassified
See 1 more Smart Citation